Redox Balance in Van Cats and It’s Association with Age, Gender and Eye Color - Bilgic, B; Özkan, C; Moscati, L; Kaya, A; Dokuzeylül, B; Kayar, A; Or, ME (Journal of the Hellenic Veterinary Medical Society, 2024)
Objectives: The aim of this study was to determine the oxidative stress index and redox balance in healthy Van cats and to evaluate it’s association with gender, age and eye color. Methods: 80 healthy Van cats from different eye color, gender and age were used in the study. All cats were grouped according to their age (A) as <12 months (A1, n=30), ≥1 and <3 years (A2, n= 22), ≥3 and <5 years (A3, n=12) ve ≥5 years (A4, n= 16); eye color (E) from left to right as blue-blue (E1, n=31), blue-amber (E2, n= 19), amber-blue (E3, n= 12), amber-amber (E4, n= 19) respectively and gender (G) as female (G1, n=43) and male (G2, n=37). Blood serum ROM (D-Roms test, Diacron; Grosseto, Italy) and PAO (Diacron, Grosseto, Italy) were analyzed and OSI was measured in all groups. Results: There was no statistically significant difference between age, gender and eye color regarding ROM, PAO and OSI in healthy Van cats. Mean ROM (H2O2/dL), PAO (HClO/ml) and OSI CarrU/(µmol HClO/ml)) were 1.79, 434.8 and 0.05, respectively ( P>0.05). Conclusions: Since oxidative stress plays a critical role as a biomarker of various diseases, determination of redox balance may provide a useful tool in healthy Van cats. It was observed that ROM, PAO and OSI were not affected by age, gender and eye color in healthy Van cats. Breed differences among cat population may lead to dramatic changes in redox balance.